2003
DOI: 10.1074/jbc.m301807200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation Enhances Mitochondrial Targeting of GSTA4-4 through Increased Affinity for Binding to Cytoplasmic Hsp70

Abstract: Recently we showed that three different isoforms of cytosolic glutathione S-transferases (GST), including GSTA4-4, are also localized in the mitochondrial compartment. In this study, we have investigated the mechanism of mouse GSTA4-4 targeting to mitochondria, using a combination of in vitro mitochondrial import assay and in vivo targeting in COS cells transfected with cDNA. Our results show that the mitochondrial GSTA4-4 is more heavily phosphorylated compared with its cytosolic counterpart. Protein kinase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
91
1
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 48 publications
4
91
1
2
Order By: Relevance
“…Bimodal targeting of CYPs and APP was facilitated by the N-terminal chimeric signal, which consists of a cryptic mitochondria-targeting signal immediately flanking the N-terminal ER-targeting signal. By contrast, a C-terminal cryptic mitochondria-targeting signal was critical for the mitochondrial translocation of cytosolic GSTs (21). We also showed that mitochondrial targeting of these proteins required the activation of a cryptic mitochondrial signal either by sequence-specific processing by a cytosolic endoprotease as in the case of CYP1A1 (14) or by PKA-mediated phosphorylation of Ser residues at positions 128 or 129 as in the case of CYP2B1 and CYP2E1 (16,18,23).…”
mentioning
confidence: 76%
See 3 more Smart Citations
“…Bimodal targeting of CYPs and APP was facilitated by the N-terminal chimeric signal, which consists of a cryptic mitochondria-targeting signal immediately flanking the N-terminal ER-targeting signal. By contrast, a C-terminal cryptic mitochondria-targeting signal was critical for the mitochondrial translocation of cytosolic GSTs (21). We also showed that mitochondrial targeting of these proteins required the activation of a cryptic mitochondrial signal either by sequence-specific processing by a cytosolic endoprotease as in the case of CYP1A1 (14) or by PKA-mediated phosphorylation of Ser residues at positions 128 or 129 as in the case of CYP2B1 and CYP2E1 (16,18,23).…”
mentioning
confidence: 76%
“…In this study, we tested four different chimeric signals, including two N-terminally truncated forms to mimic endoproteolytic cleavage in the cytosol, as in the case of CYP1A1 (ϩ5/1A1 and ϩ33/1A1), and two that are targeted to mitochondria as intact uncleaved signals, namely CYP2B1 and CYP2E1 (15,16,18,21,23), for their ability to bind different TOM receptor proteins under both in vitro and in vivo conditions. Mitochondrial targeting of both CYP2B1 and 2E1 was enhanced markedly by PKA-mediated phosphorylation at the unique target sites, Ser-128 and Ser-129, respectively (16,18).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possibility is that there is an increased mitochondrial targeting of ␣-synuclein protein during the pathogenesis of PD. In a series of previous studies we have reported an important role for post translation modifications in the mitochondrial targeting of a number of physiologically important proteins (16,17,19). We showed that mitochondrial targeting of CYP 2B1 and 2E1 requires protein kinase A-mediated phosphorylation of Ser residues at positions 128 or 129, respectively (16,17).…”
Section: Discussionmentioning
confidence: 99%